Capillary cohesion of different granular materials determined from uniaxial compression and water retention tests - Heinrich Dennis; Milatz Marius (E3S Web of Conferences, 2023)
In this conference contribution, we present and discuss the results for capillary cohesion of different granular materials determined through different approaches. First, we consider macroscopic uniaxial compression tests with varying degrees of saturation. Second, we derive theoretical capillary cohesion from the water retention curve (WRC) measured in macroscopic water retention experiments. Finally, capillary cohesion is calculated from air-water interfacial areas and solid-water interfacial areas extracted from CT images acquired during a cyclic water retention experiment. An attempt is made to link the macroscopic results of capillary cohesion based on microscopic insights from CT imaging experiments.